Chemical peelings for the treatment of actinic keratosis: a systematic review and meta‐analysis. (18th August 2020) - Steeb, T.; Koch, E.A.T.; Wessely, A.; Wiest, L.G.; Schmitz, L.; Berking, C.; Heppt, M.V.
Abstract: Background: Actinic keratosis (AK) is a common precancerous lesion of the skin that may be treated with chemical peelings. Despite their long‐standing usage and clinical experience, no evidence‐based recommendation regarding the efficacy and safety of chemical peelings for AK exists. Objectives: To systematically review and synthesize the current knowledge on chemically exfoliative peelings as interventions for AK. Methods: We performed a systematic literature research in Medline, Embase and CENTRAL and hand‐searched pertinent trial registers for eligible records until 5 August 2019. Results from individual studies were pooled using a random‐effects model or described in a qualitative synthesis. The risk of bias was estimated with the tools provided by the Cochrane Collaboration (randomized and non‐randomized trials) and the Evidence Project (single‐arm trials). Results: Four randomized controlled trials, two non‐randomized controlled trials and two single‐arm studies with a total sample size of n = 170 patients were included. Trichloroacetic acid (TCA) plus Jessner's solution showed significantly lower participant complete clearance (RR 0.36, 95% CI: 0.14–0.90, two studies, I 2 = 0%, P = 0.03) and lower lesion clearance (RR 0.92, 95% CI: 0.85–0.99, one study, P = 0.03) compared to 5‐fluorouracil (5‐FU) 5% cream. TCA as monotherapy showed lower lesion complete clearance (RR 0.75, 95% CI: 0.69–0.82, two studies, I 2 = 7%, P < 0.001) and lower mean lesion reduction per patient compared to conventional photodynamic therapy (cPDT) (MD −20.48, 95% CI: −31.55 to −9.41, two studies, I 2 = 43%, P = 0.0003). Pain was more pronounced in patients treated with cPDT in comparison with TCA (MD −1.71 95% CI: −3.02 to −0.41, two studies, I 2 = 55%, P = 0.01). In the single‐arm studies, 5‐FU plus glycolic acid showed 92% lesion clearance and phenol peeling 90.6% participant complete clearance. All studies showed a high risk for bias. Conclusions: Future high‐quality studies and a standardization of peeling protocols are warranted to determine the value of chemical peelings in the treatment of AK.